2014
DOI: 10.1177/0146621614544519
|View full text |Cite
|
Sign up to set email alerts
|

On-the-Fly Assembled Multistage Adaptive Testing

Abstract: Recently, multistage testing (MST) has been adopted by several important large-scale testing programs and become popular among practitioners and researchers. Stemming from the decades of history of computerized adaptive testing (CAT), the rapidly growing MST alleviates several major problems of earlier CAT applications. Nevertheless, MST is only one among all possible solutions to these problems. This article presents a new adaptive testing design, “on-the-fly assembled multistage adaptive testing” (OMST), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
0
40
0
5
Order By: Relevance
“…Fourth, the large sample size requirements for the 4PNO limit usability by applied researchers and future research should examine strategies for accurately recovering ς in smaller samples. Fifth, recent CAT research considered procedures for online calibration of item parameters (e.g., see Zheng & Chang, 2014).…”
Section: Itemmentioning
confidence: 99%
“…Fourth, the large sample size requirements for the 4PNO limit usability by applied researchers and future research should examine strategies for accurately recovering ς in smaller samples. Fifth, recent CAT research considered procedures for online calibration of item parameters (e.g., see Zheng & Chang, 2014).…”
Section: Itemmentioning
confidence: 99%
“…The study aims at designating at which stages the average discrimination values of items that are included in the modules can be high or low in a three-stage ca-MST implementation. It is seen that item discrimination has an average value of 0.75-0.85 and SD value of 0.27-0.30 in studies that have been carried out with parameters obtained from a real pool (Kim & Moses, 2014;Kim et al, 2015, Patsula, 1999Zheng & Chang, 2015). Hambleton and Xing (2004) carried out a study in which they identified item quality as poor ( ̅ =0.60), average ( ̅ =1.00) and best corresponding to average ( ̅ =1.40) according to a parameter value.…”
Section: Methods 21 Ca-mst Panel Assemblymentioning
confidence: 99%
“…Although the classical MST models have been implemented in practice for a long time, Zheng and Chang () recently proposed an alternative assembly strategy for MST: OMST. Like classical MST, OMST is constructed in several stages.…”
Section: A Hybrid Design Framework: Examples and Principlesmentioning
confidence: 99%